2014
DOI: 10.1155/2014/708608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose, Long-Term Roxithromycin on Airway Inflammation and Remodeling of Stable Noncystic Fibrosis Bronchiectasis

Abstract: Background. Noncystic fibrosis bronchiectasis (NCFB) is characterized by airway expansion and recurrent acute exacerbations. Macrolide has been shown to exhibit anti-inflammatory effects in some chronic airway diseases. Objective. To assess the efficacy of roxithromycin on airway inflammation and remodeling in patients with NCFB under steady state. Methods. The study involved an open-label design in 52 eligible Chinese patients with NCFB, who were assigned to control (receiving no treatment) and roxithromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…Macrolides are typically referred to as both antibiotic and anti-inflammatory. We classified them as antibiotics for the purposes of analysis, except in one case where the investigators specifically referred to the trial as testing the anti-inflammatory effect [15]. Table 2 shows an overview of the selected trials used in this review and the end-points which each trial used grouped into seven main categories.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrolides are typically referred to as both antibiotic and anti-inflammatory. We classified them as antibiotics for the purposes of analysis, except in one case where the investigators specifically referred to the trial as testing the anti-inflammatory effect [15]. Table 2 shows an overview of the selected trials used in this review and the end-points which each trial used grouped into seven main categories.…”
Section: Studiesmentioning
confidence: 99%
“…Of the 23 RCTs identified by our search, we counted 31 primary end-points (five studies used co-primary end-points: HERNANDO et al [17], BILTON et al [20] and LIU et al [15] each used two, WONG et al [18] Initial search: PubMed Clinical trials in humans published in English between 2008-2018 "bronchiectasis"…”
Section: Current End-pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Экспертами выявлено 8 систематических обзоров [65-72] и 17 исследований, относящихся к данной проблеме [36,52,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. В резюме собранных доказательств показано, что у взрослых пациентов с БЭ при длительной АБТ -как ингаляционной, так и пероральной -уменьшается число обострений, увеличивается время до очередного обострения, снижаются гнойность мокроты и одышка, однако АБТ также сопровождается нарастанием побочных эффектов и антибактериальной резистентности.…”
Section: клиническая проблема 5 имеет ли преимущества длительная (≥ unclassified
“…They demonstrated a pooled reduction in exacerbation frequency of nearly 60% with macrolide therapy (risk ratio: 0.42 (0.29, 0.61) [44] and increased time to first exacerbation, cementing their role in this disorder [45] (Table 2). A small ( n = 52) open label parallel trial comparing 150 mg/day roxithromycin to a placebo over six months found that roxithromycin significantly increased time to first exacerbation (median 264 vs. 113 days, p = 0.022), reduced sputum biomarkers of airway inflammation, and improved CT-based measures of airway thickness [46]. Type of macrolide used, dose, and duration of therapy varies amongst studies, making direct comparisons difficult.…”
Section: Treatments For Bronchiectasismentioning
confidence: 99%